KEPERCAYAAN BAGAMPIRAN ANTARA MANUSIA DENGAN MAKHLUK GAIB DI AMUNTAI - Arni Arni (Jurnal Ilmiah Ilmu Ushuluddin, 2010)
Some Banjarese living in Amuntai believe that when a baby is born, some-times he or she is accompanied by another unseen baby. In other words, thebaby is twin, one is seen, while another is unseen. The latter will appear toa certain people of his/her family. The unseen person could be good or badto them. It is believed that if the family regularly feed the unseen personwith special traditional cakes, bitter and sweet coffee, he or she will be goodto the family.